Kemampuan Pedagogical Content Knowledge Guru Ipa Kelas Viii Smp Muhammadiyah Se-Kota Surakarta Dalam Penyusunan Rpp Tahun Ajaran 2016/2017 - Maryanto, Joko; , Dra. Hariyatmi, M. Si (2017)
Teacher is a component of the education system that acts as a controller of the success of an educational program. Teacher performance is believed to be the most important factor in the achievement of quality learning. The three main pillars that serve as a knowledge base that is a teacher Content Knowledge (CK), Pedagogical Knowledge (PK), and Pedagogical Content Knowledge (PCK). This study aims to determine the ability of CK, PK, and PCK Science Teacher Class Eight SMP Muhammadiyah Surakarta in preparation of lesson plan academic year 2016/2017. This type of research is qualitative descriptive for describing the ability of PCK teachers in preparation of lesson plan. Data collection techniques in this research is the method of documentation by taking 5 lesson plan of teachers randomly. Based on the research that has been done shows that the CK ability of teachers shows the result was not good (25.20%), PK ability enough (64.92%), and the ability of PCK well (71.35%). Thus the conclusions of this study is the ability of PCK in science teacher class eight SMP Muhammadiyah city of surakarta in the preparation of lesson plan included good.